Measuring overweight and obesity: Need for harmonization and refinement - Nugent, Rachel; de Onis, Mercedes; Bhatia, Komal; Stevens, Gretchen; Martin-Prével, Yves; Eriksen, Kamilla (International Food Policy Research Institute, 2014)
The negative impact of anemia during pregnancy on birth outcomes is known, but few have examined the relative contribution of anemia prior to conception. We analyzed data on preconception anemia (PA) and birth outcomes collected prospectively from 946 mother‐infant pairs participating in a micronutrient supplementation trial in Vietnam. We used generalized linear models to estimate associations between PA, defined as a three‐level ordinal variable (coded 0,1,2) based on hemoglobin concentrations (Hb): >12 mg/dl (80% of sample), >11 to <12 mg/dl (13%), and <11 mg/dl (7%), and to adjust for potential confounders (BMI, age, education). We found negative associations between PA and birth weight (‐47 g, p=0.03), length (‐0.41 cm, p=0.02), head circumference (‐0.32 cm, p=0.03), and gestational age‐GA (‐0.29 weeks, p=0.01). After controlling for GA, the associations between PA and measures of birth size were attenuated (~0.00, p>0.10), suggesting that GA mediated the association between PA and birth size in our study population. These findings support the need for strategies and interventions to prevent and control anemia in women of reproductive age, both prior and during pregnancy, to improve birth outcomes.Supported by The Micronutrient Initiative and The Mathile Institute for the Advancement of Human Nutrition